Chimeric RNA in Cancer and Stem Cell Differentiation. (28th October 2018) - Elfman, Justin; Li, Hui
Abstract : Gene fusions are considered hallmarks of cancer which can be produced by chromosomal rearrangements. These DNA-level fusion events may result in the expression of chimeric RNAs; however, chimeric RNAs can be also produced by intergenic splicing events. Chimeric transcripts created by the latter mechanism are regulated at the transcriptional level and thus present additional modes of action and regulation. They have demonstrated importance in normal cell physiology, and their dysregulation can induce oncogenesis and impact cell differentiation. In this review, we outline proven mechanisms through which intergenically spliced chimeric RNAs are involved in carcinogenesis. We highlight their similarity to canonical chimeric RNAs resulting from gene fusions as well as their unique qualities. Additionally, we review known roles of chimeric RNA in cell differentiation and propose means through which chimeric RNAs may be valuable as stage-specific markers or as targets for expression profiling.